CONTENT OF ECOLOGICAL INTELLIGENCE IN INDONESIAN LANGUAGE TEACHING MATERIALS IN THEMATIC TEXTBOOKS IN PRIMARY SCHOOLS - Sobri, Sobri; Safi'i, Imam; Mulyani, Sri; Wahdini, Lili (Universitas Negeri Makassar, 2024)
This study aims to explore the ecological content contained in Indonesian teaching materials in thematic textbooks for grade VI primary school students. The method used is content analysis. The data source in this study is Indonesian teaching materials contained in thematic textbooks intended for grade VI students. The textbooks analyzed were purposefully selected, namely textbooks published by the Ministry of Education and Culture (2018). Data were collected through a document study of the content of the textbooks, where each topic and subtopic related to ecology was identified and categorized based on the guidelines that had been prepared. The collected data were analyzed using qualitative descriptive analysis techniques. The process of data analysis involves the stages of coding data, categorizing data, and analyzing it to see the frequency of occurrence and distribution of ecological content in textbooks. The results showed that Indonesian teaching materials in thematic textbooks contain various aspects of ecology. The ecological aspects presented include types of plants and animals, the influence of geographical conditions on life, consumption of a healthy diet for the body, economic potential in terms of natural resources, the benefits of a healthy environment for the health of the body, and how to breed living things. The results of this study can be used as material for evaluating the feasibility of textbook content.